2014
DOI: 10.1021/jo501423u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nitrogen-Substituted Methylenecyclopropanes by Strain-Driven Overman Rearrangement of Cyclopropenylmethyl Trichloroacetimidates

Abstract: . (2014). Synthesis of nitrogen-substituted methylenecyclopropanes by strain-driven overman rearrangement of cyclopropenylmethyl trichloroacetimidates. Journal of Organic Chemistry, 79 (17), 8462-8468. Synthesis of nitrogen-substituted methylenecyclopropanes by straindriven overman rearrangement of cyclopropenylmethyl trichloroacetimidates AbstractNitrogen-substituted methylenecyclopropanes have been prepared by a strain-driven Overman rearrangement of cyclopropenylmethyl trichloroacetimidates. The reaction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…Sigmatropic rearrangements involving cyclopropenylcarbinol derivatives constitute an interesting entry to diversely substituted alkylidene cyclopropanes . In 2013, Hyland and co‐workers reported that the [3,3]‐sigmatropic rearrangement of trichloroacetimidates F , derived from (2‐methylcyclopropenyl)carbinols E , provided a stereoselective access to alkylidene [ N ‐(trichloroacetyl)aminocyclopropanes] G possessing an exocyclic olefin of E configuration (Scheme ) . Although this so‐called Overman rearrangement of trichloroacetimidates F proceeds under mild conditions owing to the relief of ring‐strain, the scope is restricted to substrates E substituted by an electron‐rich or ‐neutral (hetero)aromatic group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sigmatropic rearrangements involving cyclopropenylcarbinol derivatives constitute an interesting entry to diversely substituted alkylidene cyclopropanes . In 2013, Hyland and co‐workers reported that the [3,3]‐sigmatropic rearrangement of trichloroacetimidates F , derived from (2‐methylcyclopropenyl)carbinols E , provided a stereoselective access to alkylidene [ N ‐(trichloroacetyl)aminocyclopropanes] G possessing an exocyclic olefin of E configuration (Scheme ) . Although this so‐called Overman rearrangement of trichloroacetimidates F proceeds under mild conditions owing to the relief of ring‐strain, the scope is restricted to substrates E substituted by an electron‐rich or ‐neutral (hetero)aromatic group.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution at C3 on the cyclopropene ring by methyl groups was also not tolerated because of the instability of the corresponding trichloroacetimidates F . Furthermore, attempts to convert products G into ureas by reaction of the trichloroacetamide moiety with pyrrolidine did not proceed efficiently …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recently, Hyland et al disclosed the rearrangement of trichloroacetimidates derived from cyclopropenylcarbinols bearing an electron-rich or -neutral aromatic substituent (Scheme 1, eq 2). 9 The substrates involved in these rearrangements were derivatives of cyclopropenylcarbinols lacking substituents at C3, the presence of which may have a dramatic influence on the reactivity by either raising the activation barrier 10 or inducing competitive rearrangement pathways. 9 Herein, we report our investigations on the reactivity of glycolates or glycinates A, derived from secondary cyclopropenylcarbinols, in the Ireland−Claisen rearrangement 11 with the goal of synthesizing highly functionalized and diversely substituted alkylidenecyclopropanes B, incorporating an α-hydroxy or α-amino acid subunit (Scheme 1, eq 3).…”
mentioning
confidence: 99%
“…在该反应中, 由于体系中生成的 Mg 盐可以跟酯基配位, 从而影响了反应的立体选择性, 而 通过加入稍过量的 1,4-dioxane 可以大大改善这种情况, 使体系的 dr 值提高至>95∶5(图 50). 胺酯取代的环丙烯的张力作用发生 Overman 重排制备 了氮取代的亚甲基环丙烷化合物 [56] . 反应具有很好的 普适性, 而且可以方便的制备环丙烷基脲和草酰胺等衍 生物, 为 N-取代的亚甲基环丙烷的合成提供了简便的 新方法(图 60).…”
Section: 通过控制实验 作者对这一新反应做出了机理推测unclassified